Engaging Students To Take Ownership Of Their Learning Through A Stepped Teaching Model Based On The Qurâan: Evaluation By Teachers Trained Using This Model - Badruzzaman Biplob, Khalid Been Md; M.Islam, Yousuf; Rahman, Md. Sadekur (JOURNAL OF EDUCATION SCIENCE, 2015)
Getting students to learn and be confident has always challenged teachers and educationists. With the introduction of the subject of Instructional Design, teaching is now looked upon as a stepped process through which students must be taken through. To this end many teaching models have been proposed and used by teachers all over the world. At the same time, it has been noticed that students who take âownershipâ of their learning are most likely to become independent learners. Also, with the huge rise in demand for tertiary level education all over the world and more so in developing countries like Bangladesh developing successful models to manage the wave of new students has become even more important. In Bangladesh, the increased demand is coming from rural students who have had a limited access to proper primary and secondary education available in the rural areas of Bangladesh. This has added to the challenge of being able to deliver teaching that can turn around students who have poor study and language skills. In this paper we propose a stepped teaching model based on verses from the Qurâan that talk about the brain. We apply this model to training 54 newly recruited teachers who have joined Daffodil International University in the semester of spring, 2015. The idea is the teachers should evaluate the model and if perceived effective use the model in their own teaching. We demonstrate the model in action with these teachers and share the evaluation done by them.